E-cadherin gene mutations in human gastric carcinoma cell lines. - Oda, T (1994)
Reduced expression of E-cadherin has been regarded as one of the main molecular events involved in dysfunction of the cell-cell adhesion system, triggering cancer invasion and metastasis. However, even with a sufficient amount of E-cadherin, cell-cell adhesion is sometimes lost in "diffusely invasive" human carcinomas. Ten human cancer cell lines, showing growth characterized morphologically by loose cell-cell adhesion, were analyzed for possible structural abnormalities of their expressed E-cadherin. Four of the cell lines showed strong mRNA and protein expression with no nucleotide sequence abnormalities, and mRNA was absent in four other cell lines. mRNA sequence was abnormal in the remaining two gastric carcinoma cell lines. In MKN45 (poorly differentiated adenocarcinoma), this involved a 12-bp in-frame deletion with strong expression of mRNA and protein. In KATO-III (signet ring cell carcinoma), there were four mRNA species with insertions of different sizes, among which the major transcripts (with a 7-bp insertion) caused a frameshift, and expression of both mRNA and protein was markedly reduced. In these two cell lines, DNA mutations were detected around exon-intron junctions, revealing that aberrant RNA splicing was the cause of the mRNA abnormalities. In addition, the wild-type allele of the E-cadherin locus was lost, suggesting that the E-cadherin gene had been inactivated by two hits (mutation and allele loss), similar to the mechanism for inactivation of tumor suppressor genes.